2017
DOI: 10.3847/1538-3881/aa7133
|View full text |Cite
|
Sign up to set email alerts
|

A Search for Water in a Super-Earth Atmosphere: High-resolution Optical Spectroscopy of 55Cancri e

Abstract: We present the analysis of high-resolution optical spectra of four transits of 55Cnce, a low-density super-Earth that orbits a nearby Sun-like star in under 18 hr. The inferred bulk density of the planet implies a substantial envelope, which, according to mass-radius relationships, could be either a low-mass extended or a high-mass compact atmosphere. Our observations investigate the latter scenario, with water as the dominant species. We take advantage of the Doppler cross-correlation technique, high-spectra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 55 publications
7
85
1
Order By: Relevance
“…Similarly to Gibson et al (2019), we applied the SysRem algorithm (Tamuz et al 2005) which was first demonstrated on high-resolution spectroscopy by Birkby et al (2013), and has since become a standard technique (e.g. Birkby et al 2017;Esteves et al 2017;Nugroho et al 2017;Deibert et al 2019). First, we apply SysRem to each order in the standard way, and determine a model representation of the 2D data array (time vs wavelength) as an outer product of two column vectors, before subtracting from the data and determining the next SysRem iteration.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to Gibson et al (2019), we applied the SysRem algorithm (Tamuz et al 2005) which was first demonstrated on high-resolution spectroscopy by Birkby et al (2013), and has since become a standard technique (e.g. Birkby et al 2017;Esteves et al 2017;Nugroho et al 2017;Deibert et al 2019). First, we apply SysRem to each order in the standard way, and determine a model representation of the 2D data array (time vs wavelength) as an outer product of two column vectors, before subtracting from the data and determining the next SysRem iteration.…”
Section: Discussionmentioning
confidence: 99%
“…Birkby et al 2013Birkby et al , 2017Esteves et al 2017). Each wavelength bin (4100 wavelength bin per order on average) is treated as a "light-curve" consisting of 52 frames (including the frames when WASP-33 b in the secondary eclipse phase).…”
Section: Removal Of Telluric and Stellar Absorption Linesmentioning
confidence: 99%
“…Recently, direct detection of molecular signature in exoplanet atmosphere using high-dispersion spectroscopy is one of the most widespread approach to the attempt of exoplanet characterization (e.g Snellen et al 2010;Crossfield et al 2011;Birkby et al 2013;de Kok et al 2013;Hoeijmakers et al 2015;Schwarz et al 2015;Birkby et al 2017;Esteves et al 2017). Unlike low-dispersion spectroscopy, high-dispersion spectroscopy can resolve molecular bands into individual absorption lines.…”
Section: Introductionmentioning
confidence: 99%
“…However, the discovery of super-Earths like 55 Cancri e that have hydrogenrich envelops (e.g. Tsiaras et al 2016;Esteves et al 2017) and effective temperatures above ∼ 2000 K (Demory et al 2016) have raised new questions. This is because XUV atmospheric evaporation models predict the destruction of primordial atmospheres in million year timescales for planets with initial masses of super-Earths (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we apply our model to 55 Cancri e because of its well constrained mass and radius (Crida et al 2018), its measured surface temperature distribution (Demory et al 2016) (which is also indicative of a synchronous rotation), and spectroscopic studies which are consistent with it being a terran body (Ridden-Harper et al 2016) hosting a hydrogen-rich atmosphere (Tsiaras et al 2016;Esteves et al 2017). CoRoT-7b being similar in mass and radius (Barros et al 2014) to 55 Cancri e but not being compatible with having an envelop (Guenther et al 2011;Kubyshkina et al 2018a) has been used in order to act as a control planet.…”
Section: Introductionmentioning
confidence: 99%